Antibiotic awareness campaign evaluation: A systematic review of strategy, multisectoral engagement, and community-level implementation - Setiatjahjati, Sri; Ichsan, Burhanudin; Indrayuda, Peni (Science Midwifery, 2025)
Inappropriate antibiotic use contributes to increasing antimicrobial resistance, a global health challenge. Public awareness campaigns are considered a crucial strategy for promoting rational antibiotic use. This article aims to systematically review published studies on antibiotic awareness campaigns globally, focusing on implementation strategies, multisectoral actor involvement, and community-level implementation. This review employed a systematic review of literature obtained from Scopus, PubMed, and ScienceDirect databases. The inclusion criteria were empirical studies (quantitative, qualitative, or mixed) published between 2019 and 2024 that addressed public antibiotic education campaigns. Based on the 294 identified articles, 12 selected studies were further analyzed. The results demonstrate a variety of campaign media, the predominance of short-term intervention durations, and the importance of multisectoral engagement. Studies that included pre-post evaluations of Knowledge, Attitude, and Practice were more effective in demonstrating the impact of behavioral change. Conclusions: Campaigns that are contextual, involve the community, and are supported by intersectoral collaboration have been shown to be more effective. This review recommends the need for sustainable campaigns and strategies tailored to local community characteristics, particularly in rural areas and vulnerable groups.